Outcome measurements following palatal soft tissue graft harvesting: A review - Malpartida-Carrillo 1, Violeta (2021)
Background: Free gingival graft (FGG) and connective tissue graft (CTG) are two of the most commonly techniques performed in periodontal and peri-implant plastic surgery. Although several outcome measurements have been pro posed for evaluation of palatal wound healing and patient morbidity, a comprehensive review about these variables is lacking. The objective of this review is to present comprehensive information about outcome measurements related to postoperative palatal wound healing and postoperative patient-reported morbidity after FGG or CTG procedures. Material and Methods: An electronic search of English language dental literature in the Medline database via Pub Med access was conducted from May 1994 to May 2020 following the PRISMA guidelines. Electronic search stra tegy complemented by hand search of impacting related dental journals, and the reference list of all included studies were used to complete data collection considering only clinical trials. Finally, inclusion criteria were applied to identify articles after full-text evaluation. Results: A total of 111 articles were identified. After the exclusion of 34 articles based on title and abstract evalua tion, 77 articles were full text screened. Following, 46 articles were excluded since they evaluated other surgical areas. Finally, 31 studies were selected and included for final evaluation. Outcome measurements were classified in variables collected by indexes and systems assessed professionally and patient-centered measurements. Visua lly-assessed measurements include indexes, photographs, bleeding and use of laboratory-aided measurements. Pa tients-centered outcomes comprise pain, discomfort and quality-of life, among others. Conclusions: The most commonly used outcome measurements related to postoperative palatal wound healing are hydrogen peroxide test, tissue color match, visual inspection, and bleeding evaluation. Pain perception, analgesic consumption, discomfort sensation, burning sensation, and changes in feeling habits are the most commonly used outcome measurements related to postoperative patient-reported morbidity